2023
DOI: 10.1002/appl.202200105
|View full text |Cite
|
Sign up to set email alerts
|

Power effect on the properties of copper nitride films as solar absorber deposited in pure nitrogen atmosphere

Abstract: Nowadays, copper nitride (Cu3N) is of great interest as a new solar absorber material, flexible and lightweight thin film solar cells. This material is a metastable semiconductor, nontoxic, composed of earth‐abundant elements, and its band gap energy can be easily tunable in the range 1.4–1.8 eV. For this reason, it has been proposed for many applications in the solar energy conversion field. The main aim of this work is to evaluate the properties of the Cu3N thin films fabricated by reactive radio‐frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…This method's ease, simplicity, low cost, reproducibility and sustainability make it a very attractive choice for the growth of Cu 3 N thin films. Previous studies have already reported that by modifying the bias voltage [33], the type of substrate [32], the working pressure [34], and the RF power [35], the film properties can be adjusted, allowing the variation in optical, electrical, structural, and morphological features to suit them to the desired ones depending on the application field. In addition, in our previous works, we have demonstrated the strong effect of RF power on modifying the morphological, structural, and optical Cu 3 N characteristics, intending to use them as solar absorbers for next-generation photovoltaics [19].…”
Section: Introductionmentioning
confidence: 99%
“…This method's ease, simplicity, low cost, reproducibility and sustainability make it a very attractive choice for the growth of Cu 3 N thin films. Previous studies have already reported that by modifying the bias voltage [33], the type of substrate [32], the working pressure [34], and the RF power [35], the film properties can be adjusted, allowing the variation in optical, electrical, structural, and morphological features to suit them to the desired ones depending on the application field. In addition, in our previous works, we have demonstrated the strong effect of RF power on modifying the morphological, structural, and optical Cu 3 N characteristics, intending to use them as solar absorbers for next-generation photovoltaics [19].…”
Section: Introductionmentioning
confidence: 99%